Rapid mashup development tools : second International Rapid Mashup Challenge, RMC 2016, Lugano, Switzerland, June 6, 2016, Revised selected papers /: second International Rapid Mashup Challenge, RMC 2016, Lugano, Switzerland, June 6, 2016, Revised selected papers. (2017) - Unknown
No abstract available